Pathogenic Activation of Mesenchymal Stem Cells Is Induced by the Disease Microenvironment in Systemic Sclerosis. Issue 8 (14th July 2020) - Taki, Zeinab; Gostjeva, Elena; Thilly, William; Yaseen, Bodoor; Lopez, Henry; Mirza, Maria; Hassuji, Zainab; Vigneswaran, Shivanee; Ahmed Abdi, Bahja; Hart, Amy; Arumalla, Nikita; Thomas, Gemma; et al.
Abstract : Objective: In systemic sclerosis (SSc), a persistent tissue repair process leads to progressive fibrosis of the skin and internal organs. The role of mesenchymal stem cells (MSCs), which characteristically initiate and regulate tissue repair, has not been fully evaluated. We undertook this study to investigate whether dividing metakaryotic MSCs are present in SSc skin and to examine whether exposure to the disease microenvironment activates MSCs and leads to transdifferentiation. Methods: Skin biopsy material from patients with recent‐onset diffuse SSc was examined by collagenase spread of 1‐mm–thick surface‐parallel sections, in order to identify dividing metakaryotic stem cells in each tissue plane. Adipose‐derived MSCs from healthy controls were treated with dermal blister fluid (BF) from patients with diffuse SSc and profiled by next‐generation sequencing, or they were evaluated for phenotypic changes relevant to SSc. Differential responses of dermal fibroblasts were studied in parallel. Results: MSC‐like cells undergoing active metakaryotic division were identified in SSc sections (but not control sections) most prominently in the deep dermis and adjacent to damaged microvessels, in both clinically involved and uninvolved skin. Furthermore, exposure to SSc BF caused selective MSC activation, inducing a myofibroblast signature, while reducing signatures of vascular repair and adipogenesis and enhancing migration and contractility. Microenvironmental factors implicated in inducing transdifferentiation included the profibrotic transforming growth factor β, the presence of lactate, and mechanosensing, while the microenvironment Th2 cytokine, interleukin‐31, enhanced osteogenic commitment (calcinosis). Conclusion: Dividing MSC‐like cells are present in the SSc disease microenvironment where multiple factors, likely acting in concert, promote transdifferentiation and lead to a complex and resistant disease state.